Polymorphism of the rDNA locus in the oil palm: a preliminary investigation - Farida Habib Shah (Malaysian Biochemical Society, 2013)
Plant rDNA consists of a tandemly repeated unit containing a gene for each rRNA (25s, 5.8s and 18s) and a spacer region separating the 25s and 5.8s rRNA gene. In plants, rRNA genes have been shown to have variation within the same and related species in term of copy number and the length of the repeat unit. The study of restriction patterns of plant genomes or cloned fragments of ribosomal genes has shown a size heterogeneity of the nontranscribed intergenic region in certain species such as wheat, maize and broad bean. The length heterogeneity is due to the variation in the copy number of small subrepeats. Species variation has been used for differentiating between species, populations and even individuals. This paper reports the investigation of the organisation of the rDNA of oil palm, Elaeis guineensis which includes the parental types Dura, Pisifera and the F1 progeny Tenera as well as a random samples of germplasm from Zaire, Africa. Fragments containency rDNA are isolated and cloned in pUC18